Examining The Influence of Leverage, Tax Planning, and Audit Quality on Earnings Management - Petronila, Thio Anastasia; Jonathan, Arnetha Fernanda; Juliana, Christina (Amkop Management Accounting Review (AMAR), 2025)
Earnings management refers to managerial actions aimed at selecting accounting policies to modify or influence reported earnings in order to achieve specific objectives, often related to personal interests. This study analyzes the effect of leverage, tax planning, and audit quality on earnings management. The research focuses on companies in the non-cyclical consumer sector listed on the Indonesia Stock Exchange (IDX) during 2019–2023. Using purposive sampling and casewise diagnostics, a final sample of 23 companies with 98 observations was obtained. Data were analyzed using descriptive statistics and multiple linear regression, with IBM SPSS version 27. The results show that leverage positively affects earnings management, while tax planning negatively affects it. In contrast, audit quality has no significant effect on earnings management.